Intra-abdominal hypertension and abdominal compartment syndrome in the critically ill liver cirrhotic patient-prevalence and clinical outcomes. A multicentric retrospective cohort study in intensive care. - Rui Pereira (Public Library of Science (PLoS), 2021)
Background Liver cirrhosis and ascites are risk factors for intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS); however, data is scarce. We aimed to determine the prevalence of IAH/ACS in a population of critically ill cirrhotic patients with acute medical illness in intensive care and to assess for risk factors and clinical outcomes. Methods This was a multicentric retrospective cohort study including two general ICUs and pooled data from a multicentric study between January 2009 and October 2019. Results A total of 9,345 patients were screened, and 95 were included in the analysis. Mean age was 56.7±1.3 years, and 79% were male. Liver cirrhosis etiology included alcohol in 45.3% and alcohol plus hepatitis C virus in 9.5%. Precipitating events included infection in 26% and bleeding in 21% of cases. Mean severity score MELD and SAPS II were 26.2±9.9 and 48.5±15.3, respectively, at ICU admission. The prevalence of IAH and ACS was respectively 82.1% and 23.2% with a mean value of maximum IAP of 16.0±5.7 mmHg and IAH grades: absent 17.9%, I 26.3%, II 33.7%, III 17.9%, and IV 4.2%. Independent risk factors for IAH were alcoholic cirrhosis (p = 0.01), West-Haven score (p = 0.01), and PaO2/FiO2 ratio (p = 0.02); as well as infection (p = 0.048) for ACS. Overall, 28-day mortality was 52.6% associated with higher IAP and ACS, and independent risk factors were MELD (p = 0.001), white blood cell count (p = 0.03), PaO2/FiO2 ratio (p = 0.03), and lactate concentration (p = 0.04) at ICU admission. Conclusions This study demonstrates a very high prevalence of IAH/ACS in the critically ill cirrhotic patient in intensive care. Increased IAP and ACS were associated with severity of disease and adverse outcomes and independent risk factors for IAH were alcoholic cirrhosis, hepatic encephalopathy and PO2/FiO2 ratio, as well as infection for ACS. Early diagnosis, prevention, and treatment of IAH/ACS might improve outcome in critically ill cirrhotic patients.